Sustainable energy efficient distillation columns sequence design of aromatic separation unit - Zaine, Muhammad Zakwan (2015)
Distillation operations became a major concern within sustainability challenge, which it becomes a primary target of energy saving efforts in industrially developed countries. However, there is still one problem, which is how do we improve the energy efficiency of the existing distillation columns systems by considering the sustainability criteria without having major modifications. Recently, a new energy efficient distillation columns methodology that will able to improve energy efficiency of the existing separation systems without having major modifications has been developed. However, this developed methodology was only considered the energy savings without taking into consideration the sustainability criteria. Therefore, the objective of this paper is to present new improvement of existing methodology by including a sustainability analysis to design an optimal sequence of energy efficient distillation columns. Accordingly, the methodology is divided into four hierarchical sequential stages: i) existing sequence sustainability analysis, ii) optimal sequence determination, iii) optimal sequence sustainability analysis, and iv) sustainability comparison. In the first stage, a simple and reliable short-cut method is used to simulate a base (existing) sequence. The sustainability index of the base sequence is calculated and taken as a reference for the next stage. In the second stage, an optimal sequence is determined by using driving force method. All individual driving force curves is plotted and the optimal sequence is determined based on the plotted driving force curves. Then, by using a short-cut method, the new optimal sequence is simulated and the new sustainability index is calculated in the third stage. Lastly, in the fourth stage, the sustainability index for both sequences (base and optimal) is compared. The capability of this methodology is tested in designing an optimal sustainable energy efficient distillation columns sequence of aromatics separation unit. The existing aromatics separation unit consists of six compounds (Methylcyclopentane (MCP), Benzene, Methylcyclohexane (MCH), Toluene, m-Xylene and o-Xylene) with five direct sequence distillation columns is simulated using a simple and reliable short-cut method and rigorous within Aspen HYSYS simulation environment. The energy and sustainability analysis is performed and shows that the optimal sequence determined by the driving force method has better energy reduction with total of 6.78 % energy savings and 0.16 % sustainability reduction compared to existing sequence with. In addition, the economic analysis shows that the return of investment of 3.10 with payback period of 4 months. It can be concluded that, the sequence determined by the driving force method is not only capable in reducing energy consumption, but also has better sustainability index for aromatic separation unit.